Effect of Pre-strain on Tensile Properties of Al5052-H32 under an Electropulsing Condition. (2017) - Kim, Minki; Song, Junghan; Huh, Hoon
Abstract: This paper is concerned with the effect of pre-strain on tensile properties of Al5052-H32 under an electropulsing condition. The electroplasticity of Al5052-H32 considering the pre-strain effect is investigated to confirm the formability focused on the level of flow stress and the elongation at fracture. Tensile tests for the pre-strain effect are carried out under two different conditions: pre-straining without the electropulsing and tensile testing continuously with the electropulsing; pre-straining with the electropulsing and tensile testing continuously without the electropulsing. Under the test conditions, electropulsing tensile tests were conducted at the quasi-static of 0.001 s −1 to investigate the effect of the starting point for applying electric current and that of the accumulated electrical energy on the material behavior in terms of the formability. In order to identify the pre-strain effect, the levels of the pre-strain were determined based on the uniform elongation of Al5052-H32 obtained from tensile tests without the electric current. The Digital Image Correlation (DIC) method was used to measure the strain of a specimen. The temperature history of a specimen during the test was measured by using the infra-red thermal imaging camera of FLIR-T621. Experimental results show that the elongation is enhanced as the starting point of applying electric current is delayed for uniform deformation and the elongation increases as the amount of elevated temperature increases with increasing the accumulated electrical energy.